“Tu és o viajante dos árabes e dos não-árabes”: Os limites do Dar al-Islam e suas zonas de contato em Ibn Battuta (703-770 H./1304-1369 D.C.) - Gonçalves, Patrik Madruga (2024)
This dissertation establishes an analysis of the representations of the Other within the limits of Dar al-Islam based on the account of Ibn Battuta (1304-1369/703-770). Born in the Maghreb, Ibn Battuta was an Arabized Muslim who traveled for almost thirty years across a territory spanning from the African Sahel to East Asia. After returning to his native region, led by the Marinid dynasty (c. 1244-1465), he dictated to the scribe Ibn Juzayy (d. 1357/758) what he had experienced, heard and felt. Commissioned by Sultan Abu Inan Faris (r. 1348-1358), the report was titled Tuḥfat al-nuẓẓār fī gharāˀib al-amṣār wa-ˁajāˀib al-asfār (“A Gift to Those Who Contemplate the Wonders of Cities and the Marvels of Travelling”), later known as Riḥla (Journey). Marked primarily by encounters with other Muslims, the work addresses various themes, including observations, historical events, anecdotes and interactions with illustrious figures, as well as descriptions of local customs. Among the regions visited, we can mention the Arab and Iranian lands, the Somali and Swahili coast, Greco-Turkish Anatolia, Central Asia, the Indian subcontinent and Sino-Mongolian China, as well as Al-Andalus and, through the trans-Saharan routes, the Mali Empire. Covering both the central and peripheral regions of the territory under Muslim authority, his itinerary presents an ethnically and culturally diverse community, yet interconnected by networks and traditions that reinforce its religious identity. From an Arabo-Islamic perspective, Ibn Battuta constructs different representations about Arabized and non-Arabized Muslims, as well as between Muslims and non-Muslims. In this dissertation, we analyze the traveler's experience facing the limits of Dar al-Islam (Abode or House of Islam) and its inhabitants, demonstrating both his agency and insertion in a pre-established sociocultural universe. To perform this task, we rely on theoretical-methodological frameworks linked to the concepts of practices and representations, where different discourses about the Self and the Other end up constructing terms, categories and positions, resulting in an authority dispute for the understanding of the sociocultural space. We argue that Ibn Battuta operated his narrative through affiliation with individuals and institutions within the Arab-Persian space, mobilizing his sociocultural universe to construct a representation of the Other that accommodated encounters with the new agents of Islam. We will see that, being followers of the same religion and, therefore, understood as part of the community of believers (umma), but distinct from the traveler in their physical and cultural traits, non-Arabized Muslims played an important role in the account by reshaping spaces and internalizing their groups in the House of Islam (Dar al-Islam).